2008
DOI: 10.1158/1055-9965.epi-07-2746
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Mass Ultrasonographic Screening of Hepatocellular Carcinoma among Thrombocytopenic Adults

Abstract: Thrombocytopenia has been reported as a valid surrogate for liver cirrhosis and could be used to identify groups at high risk of hepatocellular carcinoma (HCC) for ultrasonographic (US) screening. We designed this two-stage community-based screening for HCC. In 2004, subjects (ages z40 years) were invited to undergo comprehensive health examinations, with 17,551 men (ages 63.0 F 11.5 years) and 39,151 women (ages 59.9 F 11.7 years) participating. Subjects with platelet counts <150 Â 10 9 /L or A-fetoprotein (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…An increase in the incidence of PVT with increased HCC size has been noted previously [23] and was a trend in our patients, as was elevated AFP levels and tumor size. We found that thrombocytopenia, which has previously been noted in association with cirrhosis and HCC [12,13,14,29,30], was significantly different between the 2 tumor-size groups and was unexpectedly more pronounced in patients with smaller tumors than in those with the larger ones.…”
Section: Discussionsupporting
confidence: 58%
“…An increase in the incidence of PVT with increased HCC size has been noted previously [23] and was a trend in our patients, as was elevated AFP levels and tumor size. We found that thrombocytopenia, which has previously been noted in association with cirrhosis and HCC [12,13,14,29,30], was significantly different between the 2 tumor-size groups and was unexpectedly more pronounced in patients with smaller tumors than in those with the larger ones.…”
Section: Discussionsupporting
confidence: 58%
“…It has been shown that thrombocytopenia could be used to predict the development of esophageal varices [25], identify advanced fibrosis and cirrhosis in chronic HCV infection, and could also be used as a tool to identify high-risk groups of HCC [14,15,17]. The increasing (and even normalization of) platelet counts in patients with advanced fibrosis/ cirrhosis might promise less progression of liver failure and liver-related mortality [3,4], formation of esophageal varices, and HCC [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous community studies, thrombocytopenia has also been used to identify advanced fibrosis and cirrhosis in patients with chronic HCV infection [14]. In addition, thrombocytopenia could also be used as a tool to identify high-risk groups of HCC [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Half of the county governments have also provided hepatitis screening programs [4,5,20,21]. Nationwide or local foundations [22,23] have conducted screening programs.…”
Section: Community-based Screening For Hccmentioning
confidence: 99%
“…The next model of community-based screening was conducted in dual HBV- and HCV-endemic areas (model 4) [20]. AFP was shifted from the second stage to the first stage.…”
Section: Community-based Screening For Hccmentioning
confidence: 99%